Balancing the consequences of in-water cleaning of biofouling to improve ship efficiency and reduce biosecurity risk - Scianni, Chris; Georgiades, Eugene; Mihaylova, Ralitsa; Tamburri, Mario N. (Frontiers in Marine Science, 2023)
Effective environmental policy often involves introducing and maintaining important activities with positive outcomes while minimizing environmental consequences; essentially decoupling a positive activity from its negative impacts. In-water cleaning (IWC) of biofouling from ships’ submerged surfaces is an example of an activity with positive outcomes (e.g., maintaining optimal ship energy efficiency and decreased biosecurity risk) and unintended negative consequences (e.g., release of living organisms, biocides, and microplastics). Several approaches exist to mitigate these negative consequences, including debris capture, with primary and secondary treatment of removed particulate and dissolved materials. However, it is unlikely that these approaches will eliminate environmental risk. Policy makers should be aware of the full suite of risks related to ship IWC and the tradeoffs to consider when balancing mitigation approaches.